Invariance of organisational citizenship behaviour measurement model across institutions in Malaysia - Abu Hasan, Shamila; Omar, Fatimah; Khairudin, Rozainee; Mastor, Khairul Anwar Mastor; Nordin, Mohamad Sahari; Wan Husin, Wan Nurul Izza; Mohamed Zain, Azlan (Canadian Center of Science and Education, 2015)
Organisational Citizenship Behaviour (OCB) is a discretionary behaviour that benefits organisations and their members. Even though OCB has been broadly researched over the years in the US, the measurement of OCB has received rather limited deliberation particularly in Asian contexts like Malaysia. This study tests the adequacy of the OCB measurement model and analyses the invariance of the model of 417 respondents in two Malaysian institutions. A three–dimensional OCB model was found to be adequate after having been subjected to Confirmatory Factor Analysis (CFA). As a result of discriminant validity, the two dimensions of OCB ‘helping’ and ‘civic virtue’ were found to measure the same thing. Consequently, the two dimensions were merged and named ‘concern’. Although the factors were found to have acceptable reliability and validity with very few modifications, there is a need to further test the model with different and larger samples. This study also shows that the CFA model experienced invariance across institutions. The results have practical implications for recruitment and training managers to utilise the instrument as well as to pay more attention to the importance of cultivating OCB among staff of the sampled institutions.